한국 청소년의 소득계층에 따른 혈액 생화학적 특성 및 영양소섭취상태 : 제6기(2013 ~ 2015) 국민건강영양조사를 이용하여 - 권유경(Yu-Kyeong Kwon); 김숙배(Sook-Bae Kim) (Korean journal of community nutrition, 2021)
Objectives: The purpose of this study was to examine the biochemical characteristics, intake of energy, and nutrients by household income levels of Korean adolescents aged 12 to 18 years. Methods: Data from the 6th (2013 ~ 2015) Korea National Health and Nutrition Examination Survey (KNHNES) were used for the study. A total of 1,839 (966 boys, 873 girls) subjects were included, and they were divided into four income groups according to their household income level. We examined general characteristics (gender, region of residence, skipping or not-skipping breakfast, lunch, dinner, frequency of eating-out), anthropometric characteristics (height, weight, weight status), biochemical characteristics (fasting plasma glucose, blood urea nitrogen, creatinine, triglycerides, cholesterol, HDL-cholesterol, hemoglobin, and hematocrit), the quantitative intake of energy and nutrients using the Korean Dietary Reference Intakes (KDRI), and the qualitative intake evaluated by the nutrition adequacy ratio (NAR) and mean nutrition adequacy ratio (MAR) of the four groups. Results: There were significant differences by income group within the region of residence and the rate of skipping breakfast, lunch, and dinner. The low-income group had a higher rate of skipping breakfast, lunch, and dinner. According to the income group, there was a difference in the height of boys, and there was no difference in the weight and obesity of boys and girls. In the biochemical characteristics, only the hematocrit of girls showed differences by income group. The quantitative intake of energy and nutrients compared with KDRI differed by income group. There were differences in energy, carbohydrates, proteins, thiamin, riboflavin, niacin, and phosphorus levels in boys and protein, vitamin A, niacin, and sodium levels in girls. The qualitative intake of energy and nutrients examined using NAR and MAR also differed according to the income group. The NAR showed differences in calcium in boys and vitamin C and calcium in girls. The MAR revealed differences in both boys and girls by income group. Conclusions: Among adolescents in the low-income group, the rate of skipping meals was high, and the quantitative and qualitative intake of energy and some nutrients was low. It is suggested that the nutritional intake can be improved by lowering the rate of skipping breakfast, lunch, dinner. We suggest that even just providing breakfast in schools can be considered highly effective in improving the rate of avoidance of skipping meals and improving nutrient intake. Also, we suggest that it is necessary to improve the food environment, food availability, and food accessibility through national and social support for low-household income adolescents.